Nurses' Experiences of Managing and Management in a Critical Care Unit. (8th May 2014) - Ogle, K. Robyn; Glass, Nel
In this article, we describe the major findings of an ethnographic study undertaken to investigate nurses' experiences of managing nurses and being managed by nurses in an Australian critical care unit. Our purpose was to valorize and make space for nurses to speak of their experiences and investigate the cultural practices and knowledges that comprised nursing management discourses. Subjugated practices, knowledges, and discourses were identified, revealing how nurses were inscribed by, or resisted, the discourses, including their multiple mobile subject positions. Informed by critical, feminist, and postmodern perspectives, nine mobile subject positions were identified. Direct participant observation, participant interviews, and reflective field notes were analyzed for dominant and subjugated discourses. The major finding described is the subject position of "junior novice." Nurses informed by dominant patriarchal and organizational discourses participated in constructing and reinscribing their own submissive identity reflected in interprofessional relations that lacked individual valuing and undermined their self-esteem.